(untitled) (Marketing Journal, 2025)
This article explores the practical significance of marketing strategies in enhancing the competitiveness of printing enterprises. The analysis focuses on market segmentation approaches that enable the development of customer -oriented services. Results hig hlight the role of marketing tools in creating competitive advantages. Effective approaches are developed based on strategic planning, pricing, service quality, and brand positioning through digital integration.